The answers are as follows:
d = 8
e = -2
f = 3
To find d and e, we first have to factor the polynomial. You can start by pulling the greatest common factor out, which is 2.
f(x) = 2x^2 - 12x - 32
f(x) = 2(x^2 - 6x - 16)
Now we can factor the inside by finding the two numbers that multiply to the constant (-16) and add up to the middle number (-6). The numbers -8 and 2 satisfy both of these and can be used for the bases of the factoring.
f(x) = 2(x - 8)(x + 2)
Now to find the zeros, all you have to do is set each parenthesis equal to 0 separately.
FIRST ZERO
x - 8 = 0
x = 8
SECOND ZERO
x + 2 = 0
x = -2
Now to find the x value of the vertex, we can simply use the formula for x values of vertex (-b/2a), in which a is the coefficient of x^2 (2) and b is the coefficient of x (-12). Now we'll plug those values in.
-b/2a
-(-12)/2(2)
12/4
3